CASE OF COMBINED STAGED TREATMENT FOR GIANT CELL TUMOR OF DISTAL EPIPHYSIAL CARTILAGE OF RADIAL BONE - O. V. Sabodashevsky; D. A. Solodky; E. V. Seumyan (Инновационная медицина Кубани)
We present the case of successful surgical treatment in the patient with a giant cell tumor of distal epithysial cartilage of radial bone. Important feature of this case is a multi-stage combined treatment for the tumor of the radial bone with bone autotransplant in the proximal area of the peroneal bone. We discuss issues of epidemiology and choice of surgical techniques for giant cell tumor treatment.